CEFTRIAXONE-INDUCED PERIORBITAL EDEMA - ANUHYA, VINAYAKA; Nayak, Veena; Somu, Keerthi; Thomson, Sereene Rose; Bs, Sujatha (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Cephalosporins are widely prescribed antibiotics for common infections and also used for prophylactic measures. Ceftriaxone is a third-generation cephalosporin which is known to cause hypersensitivity reactions presenting in various manifestations. Periorbital edema is a rare presentation of adverse drug reaction produced by ceftriaxone. Here, we report one such adverse drug reaction produced by ceftriaxone.